G-jitter induced mixed convection adjacent to a vertical stretching sheet - Nik Mohd. Naser, Nik Nabilah (2014)
The effect of g-jitter which occurs in microgravity environment can give rise to significant convective motions which are detrimental to some experiments. In this research, the effect of g-jitter induced mixed convection adjacent to a vertical stretching sheet is studied. Specifically, problems associated with the effect of g-jitter on heat or heat and mass transfer also known as double diffusion with the effect of internal heat generation or absorption and Hall effect are investigated. The governing equations, which consist of coupled nonlinear partial differential equations, are solved numerically using an implicit finite difference scheme known as the Keller-Box method. Numerical results for reduced skin friction, heat and mass transfer coefficients for different physical parameters especially for the heat generation or absorption parameter, Q, Prandtl number, Pr, buoyancy ratio parameter, N, Schmidt number, Sc, magnetic field, M and Hall parameters, m, are calculated and presented graphically. The results indicate that values for reduced skin friction, heat and mass transfer coefficients increase when the values of heat generation or absorption parameter, Prandtl number, Schmidt number and Hall parameter increase. However, values for reduced skin friction, heat and mass transfer coefficients decrease when the values of the buoyancy ratio and magnetic field parameters increase. Meanwhile, as the Hall parameter, m, increases, the velocity in the z-direction increases gradually, until it reaches the maximum value when 1m? , and then decreases with an increasing m. Generally, our results show that low frequencies and large amplitudes of g-jitter have more influence on the flow in contrast with its high frequencies and small amplitudes